(untitled) (Research, Society and Development, 2020)
Endometriosis is a chronic estrogen-dependent inflammatory disease and is characterized by the appearance of endometrial tissue outside the uterine cavity, which may appear in the pelvic region or in other organs such as the diaphragm, lung, bladder and intestine. It affects 5 to 15% of women of childbearing age and, in Brazil, an estimated six million women are carriers of the disease. Currently, the most common treatments are surgical procedures for cauterization and removal of outbreaks of endometriosis and the use of pain relief medications. However, procedures are invasive and present risks, and medications can cause unwanted side effects. Scientific evidence has shown that diet and the adoption of healthy eating habits are able to influence the process of endometriosis. The present study aimed to analyze the influence of food on the etiology and control of the symptoms of the disease. The bibliographic search was carried out using the PUBMED and SCIELO databases and ten articles published in the last ten years were selected, whose studies were carried out in humans. After reviewing the literature, it became evident that the adoption of healthy habits may be able to reduce risks and control the symptoms of endometriosis and that the nutritionist has a fundamental role in the treatment of the disease.